The effect of variation of meteorological parameters on the tropospheric radio refractivity for minna (Global Journal of Science Frontier Research, 2012)
This paper investigates the effect of diurnal variations meteorological parameters on the troposheric radio refractivity during dry and rainy seasons for Minna in 2008. The hourly averages of radio refractivity during dry (February) and rainy (August) seasons were calculated from the data obtained from the Center for Basic Space Science (CBSS) through Omini web. This data used for the computation of radio refractivity is a five minutes interval of the variations of meteorological parameters for each day in the troposphere for Minna. The results indicated that the hourly averages of radio refractivity during rainy season (August) are greater than the results in dry season (February). This is as a result of variations in meteorological parameters such as humidity and temperature in the lower troposphere which causes the radio refractivity to vary at different time of the day.
Keywords: Meteorological parameters; Troposphere; Radio refractivity